Balancing metabolites in drought: the sulfur assimilation conundrum - Chan, Kai Xun; Wirtz, Markus (Trends in plant science, 2013)
A key plant response to drought is the accumulation of specific sets of metabolites that act as osmoprotectants, osmolytes, antioxidants, and/or stress signals. An emerging question is: how do plants regulate metabolism to balance the ‘competing interests’ between metabolites during stress? Recent research connects primary sulfur metabolism (e.g., sulfate transport in the vasculature, its assimilation in leaves, and the recycling of sulfur-containing compounds) with the drought stress response. In this review, we highlight key steps in sulfur metabolism that play significant roles in drought stress signaling and responses. We propose that a complex balancing act is required to coordinate primary and secondary sulfur metabolism during the drought stress response in plants.